Echographic Structure of the Liver in Patients with Chronic Heart Failure (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The importance of assessing the severity of chronic cardiac failure (CHF) by examining the condition of the liver and hepatic hemodynamics. Perivenular fibrosis is identified as the morphological substrate for congestive liver and cirrhosis development, which worsens the course of CHF. Ultrasonography is used to identify changes in liver size, structures, and blood flow abnormalities. However, there is a lack of literature describing ultrasonographic structural changes specific to cardiac fibrosis. The article also mentions a relationship between the pressure in the right atrium and pulsating blood flow in the portal vein. The state of the liver and hepatic hemodynamics plays an important role in assessing the severity of the condition and predicting the development of chronic heart failure(CHF). Perivenular fibrosis, which is a morphological substrate of a congestive liver and spreads deep into the hepatic lobules, passes to the periportal zones, leading to the development of cirrhosis and portal hypertension, the clinical manifestations of which aggravate the course of CHF. Ultrasonography allows you to detect an increase in size, a change in the structure of the liver, an expansion of the hepatic and portal veins. We have not found any literature data describing the ultrasonographic structural changes of the liver parenchyma characteristic of cardiac fibrosis.Characteristic changes in blood flow, determined by Dopplerography, consist in a violation of the phase of the Doppler spectrum in the hepatic veins, as well as in a decrease in the average linear velocity of blood flow and the appearance of pulsating blood flow in the portal vein. The relationship between the pressure level in the right atrium and the severity of such pulsation has been established. However, these There are insufficient data to assess the significance of portal hemodynamic disorders for predicting the course of CHF.Materials and Methods:The study included 110 patients with CHF and 33 control patients, and various examinations were conducted including echocardiography and ultrasound examination of the liver. The study aimed to assess the significance of portal hemodynamic disorders in predicting the course of CHF.Summary:General clinical and laboratory examination, eleetrocardiography, echocardiography, ultrasound and doppler examination of the liver were carried out in 109 patients with chronic heart failure and 31 patients of the control group. Portal hemodynamics parameters in chronic heart failure of the I-II functional class did not differ from those in the control group and three types of portal system reactivity are revealed in the III-IV functional classes. The most unfavorable type of portal system reaction, accompanied by progressive aggravation of state of patients by echocardiography and boderline videodensitometry is the third type of reaction.